In Loving Memory? Indecent Forgetting of the Dead in Continental Sister-Books and Julian of Norwich’s Revelation of Love - Perk, Godelinde Gertrude (Religions, 2023)
Medieval nuns and anchorites (recluses) were spiritually and economically bound to pray for the dead, no matter their feelings towards the departed, who frequently appear to them in visions. This article charts medieval enclosed women’s attempts to intervene in this economy by forgetting souls. Staging a generative conversation between medieval women’s writings and Marcella Althaus-Reid’s (1952–2009) ‘indecent theology’ (queer liberation theology), this essay scrutinizes medieval female-authored texts for indecent forgetting (socially and economically disruptive forgetting). It juxtaposes a Middle English visionary text, A Revelation of Love by anchorite Julian of Norwich (1342/1343–c. 1416), with the mid-fourteenth-century Middle High German sister-book (compilation of nuns’ lives) of the Dominican convent of St Katharinental in Diessenhofen (in present-day Switzerland) and the early sixteenth-century Middle Dutch sister-book of Diepenveen (in the present-day Netherlands), originating from a Devotio Moderna convent of Augustinian canonesses regular. Heeding Althaus-Reid’s call, it dissects how forgetting unsettles systems of sanctioned spiritual and economic exchanges. I first examine how the sister-books forget certain souls and define their own terms for their participation in this system. I then turn to how Julian enlists all believers for her intercessory duties but also misplaces souls. Throughout, this article considers how these texts prise open space for medieval women within indecent theology. Ultimately, it illustrates how medieval women’s negotiations of their economic conditions supply a fertile ground for considering larger concerns of defiance, community, and the charity that binds together the living and the dead.